2010
DOI: 10.1007/s10552-010-9705-4
|View full text |Cite
|
Sign up to set email alerts
|

A Promotora-administered group education intervention to promote breast and cervical cancer screening in a rural community along the U.S.–Mexico border: a randomized controlled trial

Abstract: A promotora-based educational intervention can be used to increase breast and cervical cancer screening utilization among Hispanic women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(130 citation statements)
references
References 16 publications
3
120
3
Order By: Relevance
“…Another promising approach to address health literacy challenges related to breast cancer screening is to use patient navigators (community health workers or promotoras) as this workforce is already embedded in many border communities and they can readily assist low literacy populations in obtaining breast cancer information. Recent studies have shown that the use of community health workers can increase mammography screening and self-efficacy as well as the level of perceived susceptibility and benefits of breast cancer screening in U.S.-Mexico border communities [22,23]. Thus, community health workers not only can help to improve health literacy levels by delivering educational materials but they can also help low literacy populations to effectively access health care services available in local communities.…”
Section: Discussionmentioning
confidence: 99%
“…Another promising approach to address health literacy challenges related to breast cancer screening is to use patient navigators (community health workers or promotoras) as this workforce is already embedded in many border communities and they can readily assist low literacy populations in obtaining breast cancer information. Recent studies have shown that the use of community health workers can increase mammography screening and self-efficacy as well as the level of perceived susceptibility and benefits of breast cancer screening in U.S.-Mexico border communities [22,23]. Thus, community health workers not only can help to improve health literacy levels by delivering educational materials but they can also help low literacy populations to effectively access health care services available in local communities.…”
Section: Discussionmentioning
confidence: 99%
“…Eight interventions were based exclusively or partly in Texas [11, 5154, 56, 67, 68, 70, 83, 91, 92], seven in California [11, 54, 6365, 85, 87, 88, 93], six in Arizona [59–61, 73, 74, 77, 78, 84, 94], four in New York [57, 58, 80, 81, 83, 89, 90, 93], and two in Washington state [7072]. Additional intervention sites included Colorado [86], New Mexico [11, 54], Arkansas [57, 58, 80, 81], Illinois [55], Virginia [69], Pennsylvania [66], Florida [62], Georgia [75, 76], and Alabama [79].…”
Section: Resultsmentioning
confidence: 99%
“…Additional intervention sites included Colorado [86], New Mexico [11, 54], Arkansas [57, 58, 80, 81], Illinois [55], Virginia [69], Pennsylvania [66], Florida [62], Georgia [75, 76], and Alabama [79]. The interventions included one-time intervention sessions or activities [57, 58, 62, 68, 72, 77, 78, 80–82, 88, 90, 94]; multiple-session or multiple-contact programs [11, 54, 59–61, 6366, 7376, 79, 84]; and programs with ongoing activities over a specified period of time, such as media campaigns, system protocol changes, or materials distribution [51–53, 55, 56, 67, 67, 69, 72, 83, 8587, 89, 9193]. Breast cancer screening was jointly targeted along with cervical cancer screening in more than half (n=18) of the interventions [11, 5156, 5865, 69, 73, 74, 77, 78, 82–84, 89, 91, 92].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that cultural norms, such as these, which present barriers to breast cancer detection can be overcome via culturally-relevant interventions (e.g., work by Lorig & Waters, 2003, Marshall et al, 2013, and Nuno, Martinez, Harris, & García, 2011). An innovative community approach by Lorig and Walters, known as the HECO (Health Education-Community Organization) approach, has been shown to positively address cultural barriers to breast cancer screening.…”
Section: Cultural Barriers To Carementioning
confidence: 99%